2011
DOI: 10.1111/j.1099-0860.2011.00372.x
|View full text |Cite
|
Sign up to set email alerts
|

Meeting the Needs of Vulnerable Young Men: A Study of Service Provider Views

Abstract: This article uses a qualitative approach to elicit the views of 31 professionals who provide services to vulnerable young men. The findings reveal six key themes following focus group interviews: (i) the importance of masculinity in explaining problematic behaviour; (ii) the misuse of alcohol and drugs; (iii) alienation and social isolation; (iv) concerns about suicide and self‐harm; (v) the quality of existing services; and (vi) recommendations for changes to services. Service providers generally acknowledged… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
10
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 28 publications
1
10
0
Order By: Relevance
“…Other research on the psychological impact of the conflict has shown that adolescents' exposure to direct and indirect violence has been detrimental to their mental health and well‐being (MacAloney and others, ), leading to negative coping mechanisms such as denial (O'Reilly and Stevenson, ). Meanwhile high levels of psychological and mental health needs often remain unmet by health and social care services (Campbell and others, ; McAlister and others, ).…”
Section: Social Exclusion In Northern Irelandmentioning
confidence: 99%
“…Other research on the psychological impact of the conflict has shown that adolescents' exposure to direct and indirect violence has been detrimental to their mental health and well‐being (MacAloney and others, ), leading to negative coping mechanisms such as denial (O'Reilly and Stevenson, ). Meanwhile high levels of psychological and mental health needs often remain unmet by health and social care services (Campbell and others, ; McAlister and others, ).…”
Section: Social Exclusion In Northern Irelandmentioning
confidence: 99%
“…Robb (2001) identified a similar ambivalence in the attitudes of male childcare workers. More recently, the notion that positive male role models are one way in which the complex needs of vulnerable and at risk young men might be addressed, has also been explored (Campbell et al 2011). Based on a study of a mixed group of thirty-one members of staff from eighteen different agencies who provide services to vulnerable young men in Northern Ireland, Campbell et al (2011) found that a number of practitioners appealed for more sensitive approaches to improve services.…”
Section: Welfare Settings and Service Interventionmentioning
confidence: 99%
“…In comparison to the UK, average mental health needs in Northern Ireland are 25% higher (Department of Health, Social Services and Public Safety, 2004). Social exclusion, as well as unemployment and under employment are also major concerns (Campbell et al, 2013: Rondo¤ n et al, 2014. Although many young people have never experienced 'the Troubles', young people in Northern Ireland face a real threat of inheriting the psychological vulnerability of their parents that was created by the con£ict (McGrellis, 2004;McAlister et al, 2009).…”
mentioning
confidence: 99%
“…Although many young people have never experienced 'the Troubles', young people in Northern Ireland face a real threat of inheriting the psychological vulnerability of their parents that was created by the con£ict (McGrellis, 2004;McAlister et al, 2009). Northern Ireland is no di¡erent in this regard, and has experienced low socioeconomic progress as a result of the ongoing presence of sectarian divisions, especially in low income, segregated communities (Davidson & Leavey, 2010;McCormick & Harrop, 2009;Rondo¤ n et al, 2014;Campbell et al, 2013). According to a report by the World Bank (2011), youth unemployment is a constant in all con£ict situations globally.…”
mentioning
confidence: 99%
See 1 more Smart Citation